2019
DOI: 10.1002/cbf.3452
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0001658 promotes the proliferation and metastasis of osteosarcoma cells via regulating miR‐382‐5p/YB‐1 axis

Abstract: Circular RNA (circRNA) can modulate the gene expression via sponging microRNA (miRNA) in multiple malignancies. Nevertheless, the detailed function of circ_0001658 in osteosarcoma (OS) and its regulatory mechanism remain elusive.Real-time PCR was carried out to detect the expressions of circ_0001658, miR-382-5p, and Y box-binding protein 1 (YB-1) mRNA in OS tissues. Besides, western blot was done to monitor YB-1 expression in OS cells. Chi-squared test was used to analyse the correlation between circ_0001658 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 42 publications
3
31
0
Order By: Relevance
“…20 Circ_0001658 boosted cellular proliferative and metastatic abilities in OS via the modulation of miR-382-5p/YB-1 axis. 21 And circMMP9 was validated to facilitate the oncogenesis of OS by restricting miR-1265 expression to up-regulate CHI3L1. 22 In this chapter, we not only discovered the abnormal overexpression of circCRIM1 in OS tissues and cells but also ascertained that circCRIM1 worked as a tumor driver of OS for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…20 Circ_0001658 boosted cellular proliferative and metastatic abilities in OS via the modulation of miR-382-5p/YB-1 axis. 21 And circMMP9 was validated to facilitate the oncogenesis of OS by restricting miR-1265 expression to up-regulate CHI3L1. 22 In this chapter, we not only discovered the abnormal overexpression of circCRIM1 in OS tissues and cells but also ascertained that circCRIM1 worked as a tumor driver of OS for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, multiple lines of evidence have clari ed that various miRNAs are implicated in regulating the osteosarcoma occurrence and development, and are abnormally expressed in cancer, functioning as oncogenes to exert effects [35]. For example, Circ_0001658 propels the proliferation and metastasis of osteosarcoma cells in way of regulating the miR-382-5p / YB-1 axis [36]. Knocking down miR-9 in human osteosarcoma cell lines inhibits their metastatic potential [37].…”
Section: Discussionmentioning
confidence: 99%
“…For example, compared with adjacent tissues, circ_0001658 displayed a significantly higher expression in OSA tissues. Hsa_circ_0001658 could impede apoptosis by sponging miR-382-5p and positively modulating Y-box binding protein 1 (YB-1) expression to facilitate the proliferation, migration, and invasion of OSA cells (33). Wu et al (44) revealed that increased circTADA2A expression in OSA tissue and cells promotes the progression and metastasis of OSA by sponging miR-203a-3p and by targeting oncogene cyclic AMP-responsive element-binding protein 3 (CREB3), both functionally and mechanistically.…”
Section: Onco-circrna (Upregulated Circrna)mentioning
confidence: 99%